FENOMENA TABU BAHASA DALAM TRADISI ZIARAH DI KAWASAN SANGHIYANG SIRAH, UJUNG KULON: SEBUAH KAJIAN ETNOLINGUISTIK - Sajali, Moh Taspan (Teks: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2024)
This study examines taboos on language taboos within the scope of the Pilgrimage Tradition in the Sanghiyang Sirah Environment Ujung Kulon. The problem studied is looking for taboo forms and uncovering the meanings implicit in language taboos. The aim of the research is to find out the forms of taboos and to find out the meaning implied in the language taboo that exists within the scope of the pilgrimage tradition in the Sanghiyang Sirah Ujung Kulon environment. The method used is the listening method and the speaking method. The collection technique in this study used the basic technique of tapping, then continued with advanced techniques, namely; speaking engagement technique, note-taking and recording techniques. The time for data collection was from January 2021 to August 2022 at the Legon Pakis Ujung Kulon Resort, Legon Pakis Village, Sumur District, Pandeglang Regency, Banten, Karang Ranjang, Legon Pakis Village, Sumur District, Pandeglang Regency, Banten, and the Sanghiyang Sirah Ujung Kulon looting site. Data analysis was carried out in three stages, namely data identification, data classification, data selection, and data interpretation. Analysis of Language Taboos in the Pilgrimage Tradition in the Sanghiyang Sirah Ujung Kulon Environment is motivated by a feeling of fear and for the sake of comfort when visiting pilgrimage sites. How to Avoid Language Taboos Within the Pilgrimage Tradition In the Sanghiyang Sirah Ujung Kulon Environment, some use euphemisms and metaphors.